Development Interactive Multimedia Using 3D Virtual Modelling on Intermolecular Forces Matter - Nurlaily Yulia Safitri; Kusumawati Dwiningsih (Universitas Islam Indonesia, 2020)
One of characteristic in chemistry is its abstractness concept thus, the models or analogies to represent its microscopic and symbolic representation which not able seen by eyes are needed. Intermolecular forces lesson is one of chemistry concept that needs microscopic and symbolic representation. Modelling for microscopic and symbolic representation can be used to facilitate students for a better learning experience. Related to the problem background, the aim of this study is to know the validity of interactive multimedia using 3D modelling. The interactive multimedia using 3D virtual modelling will contain intermolecular forces explanation and equipped with 3D illustration, animation, and text to describe microscopic and symbolic representation. This study used R&D method by Thiagarajan and the data gathering section conducted in SMA Negeri 1 Waru Sidoarjo. The instruments to assess the validities of multimedia are content validity sheet and construct validity sheet which assessed by 3 academics and practitioners. The validity average scores obtain 86.66% for content validity and 85.78% for construct validity which both categorize as “Very Valid”. Keywords: Interactive Multimedia, 3D Virtual Modelling, Intermolecular Forces